Disaster Vulnerability Assessment in Parshuram Municipality, Dadeldhura, Nepal (The Geographic Base, 2020)
This study explores the disaster vulnerability of adjoining community of Mahakali River, Parshuram municipality, Dadeldhura. A questionnaire was used to collect information on various physical, social, economic, and environmental vulnerability. Key informant interview was conducted with ward chairpersons and community disaster management committee members. Likewise, three focus group discussions were conducted with the purpose of drawing insight on different factors of disaster vulnerability in the community. Moreover, five community disaster risk management plans were reviewed to understand the types of vulnerability of community. It has been found that weak geological structure and week physical infrastructure-house, bridge, buildings are the physical vulnerability. Likewise, lack of awareness on disaster preparedness, non-implementation of building code and traditional practice are the social vulnerability. Similarly, poverty, seasonal migration, lack of irrigation and land, low quality of soil are the economic vulnerability. Heavy rainfall, forest fire, lack of conservation of water source, encroachment of wildlife inhabitants and deforestation are factors to environmental vulnerability of study area. It is found that there are various vulnerability factors that need to be minimized through the capacity enhancement.